Thromboembolism in patients with congenital afibrinogenaemia - Nagler, Michael; Kremer Hovinga, Johanna A.; Alberio, Lorenzo; Peter-Salonen, Kristiina; von Tengg-Kobligk, Hendrik; Lottaz, Daniel; Neerman-Arbez, Marguerite; Lämmle, Bernhard (Thrombosis and Haemostasis, 2016)
Frequent arterial and venous thromboembolism in patients with congenital afibrinogenaemia (CA) is neither understood nor is a safe and effective treatment established. It was our objective to report on the clinical observations and laboratory data contributing to the understanding of the frequency, physiopathology, prognosis and treatment of CA. We observed the long-term clinical course and laboratory data in a cohort of four patients with CA and thromboembolic complications, and conducted a systematic review retrieving all available data. Four patients with CA developed recurrent and extensive arterial and venous thromboembolism (TE) from an age of 25–51 years. In two patients, a treatment strategy targeting at maintaining constantly measurable fibrinogen (Fbg) levels (≥0.5 g/l) either by regular Fbg replacement or by orthotopic liver transplantation resulted in long-term remissions. Radiological imaging documented resolved arterial thrombi after 6–12 months. In contrast, recurrent thromboembolic events were observed in two other patients with infrequent Fbg replacement. A systematic review of the literature revealed 48 reports of TE in patients with CA (median age at first event 31 years), and a favourable outcome in most patients with frequent application of Fbg, aimed at constantly measurable trough levels. Present data suggests that patients with CA are at high risk of arterial and venous thromboembolic events, probably caused by thrombin excess owing to lack of thrombin scavenging by Fbg/fibrin. Regular low-dose Fbg replacement might be a safe and effective treatment option in patients with CA and thromboembolic complications.Note: Preliminary data of this report were presented as oral presentation at the XXV Congress of the International Society on Thrombosis and Haemostasis, June 20th to 25th, Toronto, Canada.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Afibrinogenaemia; venous thromboembolism; thrombosis; aortic disease; arterial occlusive disease; peripheral vascular disease; fibrinogen